Studi Senyawa Perisa pada Online Marketplaces di Indonesia: Jenis Senyawa Perisa dan Legalitasnya - Agustina, Lenny; Lioe, Hanifah Nuryani; Andarwulan, Nuri (Jurnal Teknologi dan Industri Pangan, 2024)
Various flavoring agents purchased by micro small medium enterprises (MSME) could be obtained through online marketplace. Their types and legalities have never been investigated in Indonesia. The objective of this study was to obtain an overview of the availability of the flavoring agents on online marketplace and their legality. The legality is defined as the flavoring agents which are marketed and have its compliance to regulation of Indonesian Food and Drug Agency (BPOM), otherwise is illegal. The profiles of online marketed flavoring agents on marketplace are obtained through online survey of flavorings advertisements documented using a check sheet as the tool. Tokopedia and Shopee were chosen as samples in this study because they both are the most popularly e-commerce sites clicked by consumers. A non-probability sampling and sample screening were carried out to obtain eligible samples until it achieved a predetermined amounts. There were 399 flavoring agents observed, with result of 262 legal flavoring agents (65.7%) and the rests were illegal. Mostly, they were of domestic flavorings (98.5 and 88% respectively). The cases of non-conformities forward the rules were: advertising without packaging, repacking, unregistered brands, and incompatible information in their packaging and/or labels when it was cross-checked with BPOM data. Due to the high number of illegal flavoring agents sold online, monitoring of the online flavoring markets should become a priority program of Indonesian government, while consumers need to be cautious. The traders and producer have an urgent action in taking a moral responsibility for the legality of the flavoring agents being marketed.